If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + 4a = 2a + a + 5 Reorder the terms: 1 + 4a = 5 + 2a + a Combine like terms: 2a + a = 3a 1 + 4a = 5 + 3a Solving 1 + 4a = 5 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. 1 + 4a + -3a = 5 + 3a + -3a Combine like terms: 4a + -3a = 1a 1 + 1a = 5 + 3a + -3a Combine like terms: 3a + -3a = 0 1 + 1a = 5 + 0 1 + 1a = 5 Add '-1' to each side of the equation. 1 + -1 + 1a = 5 + -1 Combine like terms: 1 + -1 = 0 0 + 1a = 5 + -1 1a = 5 + -1 Combine like terms: 5 + -1 = 4 1a = 4 Divide each side by '1'. a = 4 Simplifying a = 4
| 0.3a=51 | | 0.5b+4=2(b-12) | | 3x=25+2+2x | | 8x-2x(x+1)=2(3x-1) | | 2(9-x)=4 | | 3q+5=2q+20 | | 3p-14-19p+8= | | 2y=8-3x | | 2x-5(x-5)=-2+3x-15 | | 6+2s-8s=18 | | x^2-15y+54=0 | | -11m=-77 | | m-3=3.19 | | 20x-(2-6x)=11 | | 10m+6*0=12 | | 10x=21x+28 | | 16x=-4+-8y | | 10y-25=5 | | 10m+6*-1=12 | | -1/4(12x+8)+1/5(30x+20)= | | -5x^2+6x+7=0 | | 27-4x=-5x(4x+5)-5(-8-3x) | | 6n+4=24 | | 2(x+3)-5(2x+6)= | | 10m+6*-2=12 | | -51-11x=25-7 | | 37=18q+q | | 16x=-4+-8 | | -3+n=20 | | (7x-2)-(-3x+1)=-3(1-3x) | | 4x^4+8x^3-21x^2-32x+20=0 | | 8y-x= |